Keefektifan Model Cooperative Learning Tipe STAD dan CTL pada Materi Pokok Himpunan Ditinjau dari Kemampuan Pemecahan Masalah dan Motivasi Belajar Matematika - Husnul Laili (FONDATIA, 2017)
This study aimed to describe: 1) the effectiveness of the STAD and CTL cooperative learning model in terms of students’ problem solving ability and motivation to learn mathematics; 2) the effectiveness of the STAD type of cooperative learning model in comparison with the CTL (contekstual teaching and learning) type of cooperative learning in terms of students’ problem solving ability and motivation to learn mathematics. To find out the effectiveness of the STAD type and CTL type of cooperative learning in each variable, the data were analyzed using one-sample t-test at a significance level of 5%. To compare the effectiveness of the STAD type and CTL type of cooperative learning models, the data were analyzed using multivariate T2 Hotelling with the significance level of 5% and followed up with the univariate analysis using a with criterion bon feroni. The results of the study show that: 1) the STAD type cooperative learning models and the CTL type of cooperative learning models are effective in terms of students’ problem solving ability and motivation to learn mathematics.